2012
DOI: 10.4103/1319-2442.98149
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and depression and sleep problems among hemodialysis patients in a tertiary care center

Abstract: High prevalence of sleep problems, fatigue and depression are reported in maintenance hemodialysis (MHD) patients. To assess fatigue, depression, sleep problems and their co-relates among MHD patients in a tertiary care center in India, we studied 47 patients on MHD for >3 months. Patients demographic, medical and co-morbidity profile were recorded. Pittsburgh Sleep Quality Index (poor sleeper if score >5) and Epworth Sleepiness Scale (EPSS, abnormal daytime sleepiness if score >13) were used to assess sleep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 0 publications
5
18
1
Order By: Relevance
“…Fatigue is a frequent symptom shared by all patients on long-term dialysis ( 15 ). Joshwa et al reported fatigue in 75% of the patients on hemodialysis ( 24 ); in the current study, 65.2% of the patients had experienced fatigue.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Fatigue is a frequent symptom shared by all patients on long-term dialysis ( 15 ). Joshwa et al reported fatigue in 75% of the patients on hemodialysis ( 24 ); in the current study, 65.2% of the patients had experienced fatigue.…”
Section: Discussionsupporting
confidence: 46%
“…The validity and reliability of FSS was previously proved in a study by Zakerimoghadam ( 23 ). FSS includes nine questions rated from one to seven ( 24 ). The total score indicating the fatigue measure was calculated by dividing the sum of all scores by nine.…”
Section: Methodsmentioning
confidence: 99%
“…For this condition, in the postsurvey, the experimental group showed a large decrease, but at the follow-up survey, a slight increase was evident; meanwhile, the control group showed a gradual decrease in both the postsurvey and the follow-up surveys. In a previous study of patients on renal dialysis for 3 months or longer, 72.3% of the patients were found to have depression, with 12.6% of the patients experiencing severe depression (Joshwa et al, 2012); meanwhile, in another study, 19.3% of 400 renal dialysis patients were found to have depressive symptoms (Araujo et al, 2012). This signifies that active nursing interventions are required to reduce depression in early renal dialysis patients.…”
Section: Discussionmentioning
confidence: 95%
“…For renal dialysis patients, both mental and physical symptoms generally occur simultaneously, with depression, fatigue and sleep disorders being the most common psychopathological issues reported (Joshwa, Khakha, & Mahajan, 2012;O'Sullivan & McCarthy, 2009). In addition, as renal dialysis has important short-and long-term influences on patients' health outcomes, such as causing malnutrition, decreases in albumin levels, anaemia, and bone disease, it is necessary to understand the potential influences these factors can have on patients' health, and provide appropriate, individualised nursing (Beto, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches confirmed the high prevalence rate of depression in patients with CRF as the most common psychiatric diagnoses due to many social problems or mental stresses, which are associated with high rates of morbidity and mortality. Joshwa et al stated that the depression prevalence among these patients is 72% in India, 12% of whom suffer from severe depression (22) and in Iran the prevalence is 79% (23). Depression symptoms in chronic dialysis patients are more prevalent than other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%